Continuous Costoclavicular Brachial Plexus Block in a Pediatric Patient for Postfracture Rehabilitation - Regufe, R (2020)
The costoclavicular approach to the brachial plexus block has been recently described as a technique for anesthesia or postoperative analgesia of distal upper limb. In this article, we describe a case in which a continuous costoclavicular brachial plexus block was performed in a pediatric patient for conservative treatment of a traumatic radial fracture with severe elbow rigidity. Perineural catheter placement is a valuable option for pain control and functional prognosis during rehabilitation.